Motions of quantized vortices attached to a boundary in alternating currents of superfluid He4 - Yano, H; Hashimoto, N; Handa, A; Nakagawa, M; Obara, K; Ishikawa, O; Hata, T (2007)
The motions of superfluid vortices attached to a boundary are investigated in alternating currents by using a vibrating wire. The attached vortices appear to form a layer on the wire and enhance the mass of the wire, even for low velocity currents. In turbulence, chaotic motions of vortices such as entanglement and reconnection reduce the thickness of the layer in spite of the fact that the vortices unstably expand. When turbulence subsides, the attached vortices appear to shrink, with the degree of shrinking influenced by thermal excitations in the superfluid. © 2007 The American Physical Society.